Natureza e fins da regulação da atividade econômica - Hammerschimidt, Denise; Endlich, Kassiane Mechon M.; Scalassara, Lecir Maria; Ramos, Simone Boer; Oliveira, Valéria M. (Revista Jurídica Cesumar: Mestrado (Online), 2007)
o